The place of minorities in Uruguayan democracy - Pareja, Carlos (Universidad Centro Latinoamericano de Economía Humana (Universidad CLAEH), 2019)
This text provides some judgment elements to propose, from a long-term perspective, an alternative reconstruction of the peculiar course taken by Uruguayan democratic consolidation. This reconstruction focuses on certain crucial instances of debate about the place minorities should be granted to legitimize the exercise of democratic authority. The disputes substantiated on this matter were never unambiguously settled and remain pending until our days. In the light of such disputes, it is possible to glimpse the specific framework that underlies our process of accumulation of democratic resources, which differentiates it from those prevailing in the rest of the region.